2016
DOI: 10.1136/bmjquality.u208727.w3498
|View full text |Cite
|
Sign up to set email alerts
|

Improving the quality of operative notes by implementing a new electronic template for upper limb surgery at the Royal Derby Hospital.

Abstract: The RCS has published clear and succinct guidelines dictating the necessity for the documentation of legible and timely surgical operative notes and exactly what should be included.A baseline study within the upper limb unit at our trust showed a 71.1% adherence with the RCS guidelines with an average delay of typing of notes after dictation was 11.6 days. This quality improvement project designed and developed a bespoke electronic surgical notes template built within an existing database driven software withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 6 publications
(9 reference statements)
1
15
1
Order By: Relevance
“…Their quality audit reinforced these perceptions, as the 40 Roux‐en‐Y gastric bypass NRs they analyzed contained only 62% ± 6.6% of the variables deemed necessary for inclusion. This lack of completeness within NRs was also found in NRs for pancreatic surgery (72.5% completeness for pancreaticoduodenectomy), breast surgery (66% completeness), and upper limb surgery (71.1% completeness) . That fact that our study found a higher average QI inclusion rate (85%) compared to these other studies may reflect the greater emphasis placed on documentation at our institution.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Their quality audit reinforced these perceptions, as the 40 Roux‐en‐Y gastric bypass NRs they analyzed contained only 62% ± 6.6% of the variables deemed necessary for inclusion. This lack of completeness within NRs was also found in NRs for pancreatic surgery (72.5% completeness for pancreaticoduodenectomy), breast surgery (66% completeness), and upper limb surgery (71.1% completeness) . That fact that our study found a higher average QI inclusion rate (85%) compared to these other studies may reflect the greater emphasis placed on documentation at our institution.…”
Section: Discussionsupporting
confidence: 59%
“…This lack of completeness within NRs was also found in NRs for pancreatic surgery (72.5% completeness for pancreaticoduodenectomy), breast surgery (66% completeness), and upper limb surgery (71.1% completeness). [13][14][15] That fact that our study found a higher average QI inclusion rate (85%) compared to these other studies may reflect the greater emphasis placed on documentation at our institution. Furthermore, junior residents have an informal template that they follow when learning how to dictate reports which could partially account for the fact that junior residents had a higher QI inclusion percentage than senior residents (87% vs 80%) (P .0169).…”
Section: Discussioncontrasting
confidence: 50%
“…A subsequent re-audit, carried out after the implementation of the new electronic FC proforma, established a significant improvement in the quality of FC notes, with 100% compliance with the RCS/BAUS guidelines 1,2 in all fields. By aligning the traditional 'op-note' with a patient discharge letter we were able to not only minimise the duplication of work, but also make these clinical data easily available to all healthcare professionals within our organisation by storing it on a secured network database along with standard discharge letters.…”
Section: Discussionmentioning
confidence: 99%
“…12,15 Data collected through standardised synoptic operative records can improve patient outcomes, be used as a powerful educational tool, 12 and provide evidence for local and national audits and registries, such as the BAUS' own data project for index procedures. 2 With the growing use of EPR in the United Kingdom, standardised electronic operative records are likely to become the norm in our practice. Our FC proforma was designed specifically to be compatible with the new EPR system currently under development at our institution, with potential for future use across all Trust hospital sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation